Increasing valine, isoleucine, and total branched chain amino acids for the lactating sow - Richert, B.T.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred eighty-five sows were used to evaluate effects of the interrelationship between isoleucine and valine on sow and litter performance. Litter weight and weight gain at weaning increased as dietary valine, isoleucine, and total branched chain amino acids increased. Increasing dietary valine increased concentrations of milk DM and fat. Milk DM, CP, and fat increased as dietary isoleucine increased. Both valine and isoleucine increased litter weights. The independent increases in litter weaning weights from adding valine and isoleucine suggest separate modes of action in the lactating sow.
Keywords: Swine; Valine; Isoleucine; Lactation; Sows